2006
DOI: 10.1074/jbc.m512693200
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of mRNA Interferases from Mycobacterium tuberculosis

Abstract: mRNA interferases are sequence-specific endoribonucleases encoded by the toxin-antitoxin systems in the bacterial genomes. MazF from Escherichia coli has been shown to be an mRNA interferase that specifically cleaves at ACA sequences in single-stranded RNAs. It has been shown that MazF induction in E. coli effectively inhibits protein synthesis leading to cell growth arrest in the quasidormant state. Here we have demonstrated that Mycobacterium tuberculosis contains at least seven genes encoding MazF homologue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
158
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 129 publications
(167 citation statements)
references
References 17 publications
7
158
2
Order By: Relevance
“…We observed that the overexpression of MazF3, MazF6 or MazF9 in Mtb induced a state of reversible bacteriostasis, consistent with the results of previous studies (Fig. 1a,b) 24,26,48 . The mycobacterial strains overexpressing these MazF toxins were viable with intact membranes under aerobic conditions.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…We observed that the overexpression of MazF3, MazF6 or MazF9 in Mtb induced a state of reversible bacteriostasis, consistent with the results of previous studies (Fig. 1a,b) 24,26,48 . The mycobacterial strains overexpressing these MazF toxins were viable with intact membranes under aerobic conditions.…”
Section: Discussionsupporting
confidence: 82%
“…Our results are consistent with those of previous studies demonstrating that the overexpression of MazF toxins induces bacteriostasis in Staphylococcus aureus and E. coli 49,50 . However, in contrast to previously published studies in E. coli and Msm, the overexpression of MazF2, MazF5 or MazF7 did not affect the viability of M. bovis BCG 24,26,48 . Such variations could be due to the use of (i) different inducer-based expression systems, (ii) different host strains or (iii) vectors with different translation signals.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…Multiple chromosome-encoded TA systems have been identified 32 , and many of these contain site-specific ribonucleases. The low-specificity mycobacterial toxins MazFmt1 (UkAC) and MazF-mt6 (cleaves preferentially in U-rich regions) cause growth inhibition when heterologously expressed in E. coli, whereas MazF-mt3 (UUkCCU, CUkCCU) and MazFmt7 (UkCGCU) show almost no effect 16,33 . PemK Sa (UkAUU) induces an intermediate effect when expressed in E. coli, inhibiting growth in liquid, but not on solid media.…”
Section: Discussionmentioning
confidence: 99%
“…We have reported that seven M. tuberculosis genes encode the proteins homologous to MazF, the toxin in Escherichia coli mazEF TA system. Four of the MazF homologues, Rv2801, Rv1991c, Rv0659c and Rv1102c, were identified as toxins, among which Rv2801c and Rv1102c were characterized as ribonucleases cleaving RNA in a sequence-specific manner [8]. An open reading frame (ORF) locates immediately upstream of Rv199c and overlaps with Rv1991c by 7 base pairs.…”
Section: Introductionmentioning
confidence: 99%